2018
DOI: 10.1017/ice.2018.168
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Acinetobacter baumannii OXA-23 in old and new intensive care units without transfer of colonized patients

Abstract: Molecular heterogeneity of Acinetobacter baumannii isolates during seasonal increase in prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Two studies involved different Brazilian regions (9.5 %) [38,39]. The prospective design (9/21; 42.8 %) [13,23,25,27,29,36,37,40,41] was more common than retrospective (5/21; 23.8 %) [31,32,34,38,39]. Five case reports were also included (5/21; 23.8 %) [11,24,26,30,33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies involved different Brazilian regions (9.5 %) [38,39]. The prospective design (9/21; 42.8 %) [13,23,25,27,29,36,37,40,41] was more common than retrospective (5/21; 23.8 %) [31,32,34,38,39]. Five case reports were also included (5/21; 23.8 %) [11,24,26,30,33].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the states where the studies were conducted, the most frequent were Parana [13,33,34] and Minas Gerais [27,29,35], each with 3 studies (3/21; 14.3 %). The state of Paraná was where the first CRAB outbreak occurred in two different hospitals, making this a "model state" to study the resistance dynamics of this XDR bacterium in Brazil (Anvisa, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study suggests that the risk factors associated with A. baumannii infection that may influence both the rates of resistance and spread in the ICU includes: having comorbidities, undergoing invasive procedures, prolonged hospitalization, previous exposure to many classes of antimicrobials and old age [ 12 , 21 ]. A study carried out in several countries also linked these risk factors to a higher prevalence of infections and colonization of A. baumannii in the ICUs; moreover, seasonality was cited as a considerable risk factor in warmer seasons [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent environmental contamination and HCW infection may be possible sources of carbapenem-resistance in both Klebsiella pneumoniae and Acinetobacter baumannii . 10 , 11 Several studies have shown the genetically similarity between strains isolated from the patients, HCWs, and the environment. 5 , 11 However, the origin of transmission between patient, HCW, and environment remains unknown, and thus should be elucidated in the future.…”
Section: Discussionmentioning
confidence: 99%